2011
DOI: 10.1007/s00253-011-3446-5
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a novel promoter for efficient protein expression by Aspergillus oryzae in solid-state culture

Abstract: A novel promoter from a hemolysin-like protein encoding the gene, hlyA, was characterized for protein overexpression in Aspergillus oryzae grown in solid-state culture. Using endo-1,4-β-glucanase from A. oryzae (CelA) as the reporter, promoter activity was found to be higher than that of the α-amylase (amyA) and manganese superoxide dismutase (sodM) genes not only in wheat bran solid-state culture but also in liquid culture. Expression of the A. oryzae endoglucanase CelB and two heterologous endoglucanases (Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 21 publications
1
16
0
1
Order By: Relevance
“…The strong cellulase over-expression that tends to occur in the early fermentation stage such as within 24 hours could be attributed to the characteristics of the hlyA promoter in most cases. The similar phenomenon had been reported by Bando et al [14], who firstly showed that the endoglucanase gene expressed under the control of the hlyA promoter would give a continued increase of endoglucanase activity within the 48 hours but a gradual decrease after 48 hours. Besides, the introduction of celC gene attributed to a particular phenomenon in FPAase activity of D1-B1 that FPAase activity of D1-B1 showed a sharp increase during the later fermentation stage from the 5 th day to the 7 th day.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The strong cellulase over-expression that tends to occur in the early fermentation stage such as within 24 hours could be attributed to the characteristics of the hlyA promoter in most cases. The similar phenomenon had been reported by Bando et al [14], who firstly showed that the endoglucanase gene expressed under the control of the hlyA promoter would give a continued increase of endoglucanase activity within the 48 hours but a gradual decrease after 48 hours. Besides, the introduction of celC gene attributed to a particular phenomenon in FPAase activity of D1-B1 that FPAase activity of D1-B1 showed a sharp increase during the later fermentation stage from the 5 th day to the 7 th day.…”
Section: Resultssupporting
confidence: 85%
“…Heterogeneous cellulase expression in this study was controlled under the promoter from a hemolysin-like protein gene ( hlyA gene promoter). It has been demonstrated that high-level protein expression under the control of hlyA promoter can not be repressed by glucose not only in solid-state culture of A. oryzae but also in liquid culture [14]. A. oryzae A-4 is a good platform that can be engineered for an efficient CBP scheme after only several modifications rather than de novo introduction of complete metabolism pathway.…”
Section: Introductionmentioning
confidence: 99%
“…The same expression pattern has been reported for another almost identical protein, aegerolysin from the black poplar mushroom Ag. aegerita (Fernandez Espinar and Labarere 1997), while some bacterial (Barloy et al 1998) and ascomycetal (Bando et al 2011) aegerolysins appear to be related to bacterial and fungal sporulation, respectively.…”
Section: Activities Of the Aegerolysin Proteinsmentioning
confidence: 97%
“…This suggests that the hlyA promoter is activated by conditions or factors that are not restricted to sporulation. Indeed, Bando et al (2011) identified four putative CCAAT sequences, six putative Saccharomyces cerevisiae heat-shock transcription factor binding sequences (AGAAN), and two putative BrlAbinding sequences (MRAGGGR) that affected transcription. The CCAAT sequence is one of the most common cis elements in the promoter regions of numerous eukaryotic genes.…”
Section: Aegerolysins As a Species Determination Toolmentioning
confidence: 99%
See 1 more Smart Citation